Analisis Dampak Perekonomian Industri Batik Menggunakan Metode Swot Di Kecamatan Pasar Kliwon Surakarta - Susanti, Susi, Siti Nandiroh, S.T., M.Eng, Indah Pratiwi, ST., MT (2015)
Batik is one of the hallmark for the nation, because batik is batik clothing and historical heritage is the national dress of the country. Batik contribute to the economy and the income of the people so as to provide a positive economic impact. Solo City is one of the largest batik producer in the country. This study aims to answer the problems that have been mentioned in the above problem formulation. Thus the purpose of the study determine the economic contribution to society, and determine the internal and external factors. Benefits from this research can provide input to the company regarding the impact of the economy and determine the factors internal and external to the company. The research location was in District Kliwon Market and the object of research is the batik industry. Data collection techniques literature. Data collection questionnaire with 19 respondents batik industry. Completion using descriptive analysis and SWOT analysis (Strength, Weaknesses, Opportunities, Threats). Batik industry research results largely positive impact rising so as to provide economic development for the government, business owners and employees, and can improve the standard of living for the people around. While the results of the SWOT analysis included in quadrant 1, namely the aggressive position so that the strategies to be used is optimally utilize the strengths and opportunities, a strategy that most priority is to maintain the quality of products and expand marketing network